58 An innovative patient driven protocol for the development of a crisis preparedness toolkit: CMU-CARES [Crisis Avoidance for Rural Elderly Stakeholders]. (16th November 2020) - Varriano, Brenda; Dickinson, Averie; Mouzoon, Raha; Long, Jacob; Lu, Ruoxi; Beatty, Andrea; Ragina, Neli; Pandey, Jyotsna
Abstract : The COVID-19 pandemic challenged society, requiring measures that impacted communities socially and economically. Rurally dispersed older adults [RDOA] have a greater number of health comorbidities, poorer finances and limited access to internet and community resources (e.g. healthcare specialists), leaving them more vulnerable in a crisis. Current guidelines are better suited to urban communities, neglect certain needs of RDOA, and are at times difficult to navigate/access due to their online formats. RDOA specific resources are warranted and development should involve stakeholders. CMU-CARES sought to develop an innovative protocol that would engage RDOA in the development of a crisis preparedness toolkit. CMU-CARES protocol consists of six stages. (1) Awareness by community-based outreach (e.g. mailed-letters, social media, community organizations) and participation from older adults in previous studies with the college of medicine. (2) Engagement occurred once a participant expressed interest. (3) Screening was completed at time of engagement. (4) Interviews/Interactions were modified from the WHOQOL-BREF and completed via Web-Ex online software to observe social distancing requirements. (5) Transcript analysis was completed with NVivo software to identify participant identified themes. (6) Design and development of a toolkit based on interviews. A target sample limited to 20–25 RDOA was used to reach data saturation. Presently 20 interviews have been completed. Preliminary themes include the need for timely and reliable information, training in use of technology and the need for social interaction. Overall, CMU-CARES is a novel person-centered project dedicated to improving well-being and healthcare outcomes in the vulnerable RDOA population during crises. It hopes to foster camaraderie between healthcare providers and the community while inspiring medical student driven research and fostering careers in geriatrics, primary care and public health policy.